Supportive Legislation, Unsupportive Employers and Collective Bargaining in New Zealand / Supportive Legislation, Unsupportive Employers and CollectiveBargaining in New Zealand - Foster, Barry; Rasmussen, Erling; Murrie, John; Laird, Lan (Relations industrielles / Industrial Relations, 2011)
In New Zealand in the 1990s, labour market decentralization and new employment legislation precipitated a sharp decline in unionism and collective bargaining coverage; trends that continued well into the 2000s even after the introduction of the more supportive Employment Relations Act 2000 (ERA). The ERA prescribed new bargaining rules, which included a good faith obligation, increased union rights and promoted collective bargaining as the key to building productive employment relationships (Anderson, 2004; May and Walsh, 2002). In this respect the ERA provided scope for increased collective bargaining and union renewal (Harbridge and Thickett, 2003; May, 2003a and 2003b; May and Walsh, 2002). Despite these predictions and the ERA's overall intent, the decline in collective bargaining coverage begun in the 1990s has continued unabated in the private sector. It has naturally been questioned why the ERA has not reversed, or at least halted, this downward trend. So far research has focused on the impact of the legislation itself and much less on employer behaviour and perceptions, or on their contribution to these trends. This article addresses the paucity of employer focused research in New Zealand. The research explores views of employers on the benefi ts of collective bargaining, how decisions to engage or not engage in collective bargaining are made and the factors instrumental to them. It is demonstrated that the preferred method of setting pay and conditions continues to be individual bargaining. This is especially so for organizations with less than 50 employees, by far the largest majority of fi rms in New Zealand. Frequently, these smaller organizations see no perceived benefits from collective bargaining. Overall, these fi ndings suggest that despite a decade of supportive legislation there are few signs that the 20 year decline in collective bargaining coverage in New Zealand will be reversed.